Determinant Factors of Innovative Work Behavior in MSMEs in the Digital Era: Systematic Literature Review - Landreas Utama Lie; Sudarmiatin Sudarmiatin; Agus Hermawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to systematically review the determinants of innovative work behavior in MSMEs in the digital era in Indonesia. The research method uses Systematic Literature Review (SLR) with the design of the PRISMA framework. The data sources used were obtained from various databases of quality scientific publications including emerald, taylor and francis, springerlink, and sciencedirect, with a time range from 2020 to 2025. A total of 15 international scientific articles published in the period were analyzed for further identification of the main trends, main topics, and research directions. The results of the study show that the results of the study show that three main components consist of Innovative Work Behavior Determinants (PKI) in Micro, Small, and Medium Enterprises (MSMEs) in the modern era: Organizational/Interpersonal Factors, Leadership Factors, and Individual Factors. This Systematic Review serves as a comprehensive summary of evidence that collectively corroborates individual findings, increases confidence in applicable practices, and directs MSME strategies to ensure survival and competitive advantage amid the challenges of the digital age.